On the primitive irreducible representations of finitely generated nilpotent groups - Tushev, A.V. (Доповіді НАН України, 2021)
We develop some tecniques whish allow us to apply the methods of commutative algebra for studing the representations of nilpotent groups. Using these methods, in particular, we show that any irreducible representation of a finitely generated nilpotent group G over a finitely generated field of characteristic zero is induced from a primitive representation of some subgroup of G. Розвивається підхід, що дає змогу застосовувати методи комутативної алгебри до вивчення зображень нільпотентних груп. Із застосуванням цього підходу, зокрема, показано, що усяке незвідне зображення скінченно породженої нільпотентної групи G над скінченно породженим полем нульової характеристики є індукованим з примітивного зображення деякої підгрупи групи G.